ACCURATE THE DIRECTION OF QIBLA MOSQUE IN THE ISLAND OF A THOUSAND MOSQUES USING THEODOLITE - Ani Wafiroh (Universitas Islam Negeri (UIN) Mataram, 2019)
Lombok Island is famous for its Thousand Islands mosque. This is because on the island of Lombok there are very many mosques, almost every neighborhood (RW) has a mosque and it is not uncommon to find 2 large mosques facing or next to each other. Of the many mosques on the island of Lombok, there are several mosque buildings facing west, and there are also facing west leading north. This shows the difference in Qibla direction, so the need for calculations and re-measurements.